2003
DOI: 10.1128/aem.69.4.2330-2339.2003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Frequency Resonance Energy Transfer Pair on Double-Labeled Microsphere and Bacillus anthracis Spores by Flow Cytometry

Abstract: Development of an ultrasensitive biosensor for biological hazards in the environment is a major need for pollutant control and for the detection of biological warfare. Fluorescence methods combined with immunodiagnostic methods are the most common. To minimize background noise, arising from the unspecific adsorption effect, we have adapted the FRET (frequency resonance energy transfer) effect to the immunofluorescence method. FRET will increase the selectivity of the diagnosis process by introducing a requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
0
25
0
2
Order By: Relevance
“…Preliminary characterization has shown that the antibody has no cross-reactivity with other phylogenetically related Bacillus spores (Fig. 3), demonstrating improved specificity compared to that of polyclonal antibodies generated in our group by means of the same exosporium fraction (27). As demonstrated in our previous work, implementation of the polyclonal antibodies for specific detection of B. anthracis was achieved solely by using a double-staining method (fluorescence resonance energy transfer), whereas the scFv antibody enabled direct specific detection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Preliminary characterization has shown that the antibody has no cross-reactivity with other phylogenetically related Bacillus spores (Fig. 3), demonstrating improved specificity compared to that of polyclonal antibodies generated in our group by means of the same exosporium fraction (27). As demonstrated in our previous work, implementation of the polyclonal antibodies for specific detection of B. anthracis was achieved solely by using a double-staining method (fluorescence resonance energy transfer), whereas the scFv antibody enabled direct specific detection.…”
Section: Discussionmentioning
confidence: 99%
“…This high-molecular-weight band is probably the Bcl1 protein, known as the most immunogenic antigen of the exosporium fraction (14,20,22). The affinity constant of the purified scFv antibody was determined via FCM as demonstrated previously (18,27). In short, mean spore fluorescence at steady state was measured as a function of the antibody concentration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations